The Relationship Between Personal Factors of Mothers Under Five and The Incidence of Stuntinging in Toddlers (24-59 Months) - Meylani, Meylani; Astuti Siregar, Sri; Rahayu Ningsih, Vinna; Mawarti Perdana, Silvia; Wisudariani, Evy (Rifa'Institute, 2023)
Introduction: Stunting is a chronic nutritional problem caused by multi-factorial and intergenerational with causative factors such as malnutrition experienced by mothers during pregnancy, poverty, underage maternal pregnancy, IUGR, premature or premature birth, and babies born with low birth weight. Objective: This study aims to determine the relationship between the history of Chronic Energy Deficiency (CED) and Anemia in mothers under five with the incidence of stunting in toddlers (24-59 Months) in Sungai Mengkuang Village, Bungo Regency in 2022. Method: The type of research is quantitative with a cross sectional design, with a population of all mothers under five in Sungai Mengkuang Village, with sampling techniques using Purposive sampling techniques. The data obtained were analyzed by the Chi-Square test. Result and Discussion: The Chi-square test shows that there is a relationship between the history of CED, Anemia, Knowledge, and Parenting in mothers under five with the incidence of stunting in toddlers (24-59 months) in Sungai Mengkuang Village in 2022 with P-Value values of 0.001, 0.006, 0.012 , 0.002 respectively and there is no relationship between the attitude of mothers under five towards CED and anemia with the incidence of stunting in toddlers (24-59 months) in Sungai Mengkuang Village in 2022 (P-Value 0.606). Conclusion: In this study, there is a relationship between CED, anemia, knowledge, and parenting with the incidence of stunting in toddlers (24-59 months) in Sungai Mengkuang Village in 2022, and attitudes are not related